CD133, CD44, and ALDH1A1 as cancer stem cell markers and prognostic factors in epithelial ovarian cancer (Faculty of Medicine Universitas Indonesia, 2019)
BACKGROUND Ovarian cancer is a heterogeneous disease, and most patients are diagnosed at an advanced stage. Epithelial ovarian cancer type II is characterized by rapid tumor growth and is genetically more labile than type I. This study was aimed to demonstrate the prognostic value of CSC by using the markers CD133, CD44, and ALDH1A1 in EOC. METHODS Clinicopathological and demographic data were collected from medical records. The markers CD133, CD44, and ALDH1A1 were examined with flow cytometry and immunohistochemistry. Cancer stem cell (CSC) marker expression in patients with ovarian cancer types I and II were related to chemotherapy and survival. In multivariate analysis, the prognosis model was tested for ten months. RESULTS The largest demographic consisted of patients aged ≥45 years, with stage I, poor differentiation, and type II, of which there were 40 samples (72.7%), 23 samples (41.8%), 30 samples (54.5%), and 16 samples (29.1%), respectively. There is a high correlation between the 10-month chemotherapy response and the 4 variables, i.e., age ≥45 years, type II, stage III–IV, and CD44, with an ROC of 80.75% and a post-test probability of 82.5%. Using the ROC curve, the highest chemoresistance score was 0.841, based on the combination of CSCs markers and clinicopathological factors, that is stage III–IV, age ≥45 years, poor differentiation, type II, negative CD133, high CD44, and high ALDH1A1. CONCLUSIONS CSC (CD133, CD44, and ALDH1A1) markers and clinicopathological factors are prognostic of epithelial ovarian cancer.